PENGARUH BIMBINGAN AJARAN TAREKAT QODIRIYAH NAQSYABANDIYAH PONDOK PESANTREN SURYALAYA TERHADAP AKHLAK MAHASISWA - Sally Badriya Hisniati (Pelita Nusa Jurnal, published by the Institute for Research and Community Service (LP2M) of the Pelita Nusa Islamic Religious College West Bandung (STAI PENUS), 2021)
ABSTRACTUniversally a student is someone who has a very noble position and function, as an agent of change, moral force, social control and self-efficacy. Since they have an intellectual responsibility, the guidance program will determine the success of the student be in a society that is ready to contribute to the sustainability of the nation's welfare and progress in various sectors. The purpose of this study is to test the hypothesis and find out 1) the guidance program on the teachings of the Suryalaya Qodiriyah Naqsyabandiyah (TQN) Order to students, 2) efforts to improve the positive character of students and 3) the influence of TQN Suryalaya Teaching guidance to students at the Institute of Islamic Religion and Institute of Economic Science of Latifah Mubarokiyah at the Islamic Boarding School Suryalaya. This study uses a quantitative approach with the correlative method. The sampling technique used in this study is a simple random sampling technique. Sampling is taken from a population of final semester students which involved a sample of 183 students from a total of 338 final semester students, 136 Islamic Institute students and 47 Latifah Mubarokiyah Institute of Economic Science students. The technique of data collection uses a Likert scale questionnaire; while the technique for data analysis uses Pearson products of moment correlation, determination test, significance test, and regression test. The TQN Suryalaya teachings have some basic teachings, namely the practice of dhikr, completion (khatam), virtues (manaqib), night prayer (qiyamul lail) and pilgrimage. In addition there are practices in terms of behavior (morals) such as morality to God, morality to teachers (morshed), morality to others, morality to oneself, morality to the environment and how to instil the attitudes of taking care of (muraqabah) conditions. The influence of the TQN Suryalaya Teachings can have a positive influence on social life in the community, which includes two aspects, namely in the religious life and social life by bringing out good behaviour and attitudes, adhering to the existing norms, establishing harmonious relationships in society and nationality. The results of the study showed that the guidance of Suryalaya's TQN Teaching was in the good category at 75.69%. The moral description of students at the Islamic Institute of Religion and the Institute of Economic Science of Latifah Mubarokiyah in Suryalaya Tasikmalaya Islamic Boarding School is in good category at 74.30%. Guidance on the teachings of TQN Suryalaya is strongly and positively correlated with the morals of students with a correlation coefficient of 0.652 and a coefficient of determination of 0.452, which means that improving the quality of guidance in the Teaching of the Qodiriyah Naqsyabandiyah Suryalaya Order will be followed by positive student morals. And conversely, the decline in the quality of guidance in Suryalaya's TQN Teaching will be followed by the student's morality of 45.2%. Keywords: Guidance, Tarëqat Qodiriyah Naqsyabandiyah, Morals.